Developing a unified orthography for Berawan: An endangered Bornean language - Burkhardt, Jey Lingam *; Burkhardt, Jurgen Martin (John Benjamins Publishing, 2020)
Berawan is a small ethnic community, numbering fewer than 4,000 members, in the Malaysian state of Sarawak on Borneo Island. There are four language varieties; namely, Long Jegan (LJG), Batu Belah (BB), Long Teru (LTU) and Long Terawan (LTN). This paper describes the development of the preliminary unified Berawan orthography by the authors, in collaboration with representatives from three Berawan communities (BB, LTU and LJG). Smalley’s ( 1959 , 1965 ) criteria for orthography development are discussed in relation to the authors’ stage framework for orthographic development, which has been adapted from Rempel (1995) within the context of developing the Berawan orthography and the orthographic decisions made by the Berawan. Two additional factors for orthography implementation are proposed. The first stresses the importance of adequate testing, which is essential for both obtaining objective measurements to inform decision making and establishing a well-designed and effective orthography. The second new factor emphasizes the importance of having sufficient time available to learn the developed orthography.